2017
DOI: 10.1016/j.jstrokecerebrovasdis.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Prestroke CHA2DS2-VASc Score and Severity of Acute Stroke in Patients with Atrial Fibrillation: Findings from RAF Study

Abstract: Acciarresi, M. et al. (2017) Prestroke CHA2DS2-VASc score and severity of acute stroke in patients with atrial fibrillation: findings from RAF study. Journal of Stroke and Cerebrovascular Diseases, 26(6), pp. 1363-1368. (10.1016/j.jstrokecerebrovasdis.2017 There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/138063/ AbstractBackground and Purpose: The aim of this study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…to predict vascular events, mortality, and functional outcomes in patients experiencing AF-related stroke events. Although originally used for thromboembolic risk assessment in AF outpatients, the CHADS 2 score and its updated version, CHA 2 DS 2 VASc, can be used to effectively predict the prognosis of an AF-related stroke event (2)(3)(4)(5)(6). However, these models are simplified and do not incorporate clinical and laboratory parameters such as the severity of stroke symptoms at admission, serum inflammatory markers, and image-based features derived from the early stages of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…to predict vascular events, mortality, and functional outcomes in patients experiencing AF-related stroke events. Although originally used for thromboembolic risk assessment in AF outpatients, the CHADS 2 score and its updated version, CHA 2 DS 2 VASc, can be used to effectively predict the prognosis of an AF-related stroke event (2)(3)(4)(5)(6). However, these models are simplified and do not incorporate clinical and laboratory parameters such as the severity of stroke symptoms at admission, serum inflammatory markers, and image-based features derived from the early stages of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigations have reported that the prevalence of AF dramatically increases with age ( Bapat et al, 2018 ). AF causes a high risk of disability and death ( Acciarresi et al, 2017 ), which places a heavy burden on individuals and the healthcare system. It has been reported that the underlying mechanisms of the occurrence and maintenance of AF are regulated by genetic factors, particularly single nucleotide polymorphisms (SNPs) ( He et al, 2018 ; Lin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%